(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The decoctions of Coccinea grandis (L.) and Centella asiatica (L.) leaves were evaluated for their antidiabetic and antioxidant potentials in alloxan-induced rat model and by DPPH free radical scavenging assay, respectively. Graded doses of the decoctions administered to normal and experimental diabetic rats for two weeks showed significant reduction in fasting blood glucose levels in the normal as well as in treated diabetic animals. The experiment showed 188.42 ± 1.2 mg/dl glucose and 117.78 ± 11.2 mg/dl cholesterol levels for C. grandis, while 187.23 ± 0.8 mg/dl glucose and 116.14 ± 1.5 mg/dl cholesterol for C. asiatica. Although, the decoctions produced significant effect on serum urea level, the total protein and liver enzymes (SGOT and SGPT) were found to be normal. Acute toxicity studies showed that both the decoctions were safe at 2-fold high dose when compared with the commonly used antidiabetic dose. Total phenolic contents in decoctions were found to be 12.45±0.52 and 8.32 ± 0.31 for C. grandis and C. asiatica, respectively while DPPH free radical scavenging assay showed the IC50 values of 0.14 ± 0.001 for C. grandis and 0.17± 0.001 for C. asiatica. Our current studies for the first time, justified the use of decoctions of the leaves of C. grandis and C. asiatica for treating diabeties, hyperlipaedemia and atherogenic lesion in the indigenous system of medicine. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22322 Bangladesh Pharmaceutical Journal 17(1): 86-91, 2014